The «smart city» concept: fixing key concepts in the context of providing the development of a big municipality - A. O. Andriіenko (Aspekti Publìčnogo Upravlìnnâ, 2018)
The article reveals the content and explores the conceptual-categorical apparatus of the problem of the «smart city» formation on the territory of a large municipal entity. The classification of big municipalities, aimed at their services (communal, educational, medical, public) ‘smartization’, by type, is given. It is determined that smart cities are considered by the world scientific community from two positions: on the one hand, as objects of the spontaneous socio-economic movement, which cannot always be directed in a given strategic direction; on the other hand, as a managerial category – cities that effectively use all available information for better understanding and control of their functions and optimal use of resources available, including the potential of residents. A system of factors, the development of which is aimed at forming the foundations of a smart city, is given. The basis for developing such a system is the concept of sustainable development. Accordingly, the complex of the following factors influencing the ‘smartization’ of urban development is presented: technological (determines the level of development and public availability of digital technologies in urban services); human (creates a space for creativity, learning, obtaining and generating knowledge); economic (outlines the limits of economic capacity of the city, the coordination of economic tasks with social priorities and environmental needs); institutional (forms the basis for proper management of the city’s integrated development, promotes the development of the smart community and the attraction of intellectual capital). The criteria for meeting the goals of smart city management that outline the content and determine the directions of smart administration on the basis of sustainability are given; the factors of the formation of such a city (institutional, social, economic, technological) are presented and structured; accordingly, the concept of «smart city» is defined through the prism of institutional, social, economic, technological and integrated managerial approaches.